Dispute Resolution Model of Druwe Mrajan Land Rights from Different Religious Heirs in Badung Regency - I Gusti Agung Yoga Bhaskara Susila; I Made Suwitra; Ni Made Jaya Senastri (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
Customary land in Bali has a very close relationship with the daily life of indigenous people in Bali. Until now, inheritance disputes still occur a lot in Bali, especially seeing the economic value of customary land in Bali today, it also triggers people who have converted from Hinduism to have the same rights as those who are still Hindus in terms of inheritance regardless of the various obligations that must be carried out in Balinese Customary society. The objectives of research are to explore and identify the temple land / Druwe Mrajan land which is still sustainable today, and find court decisions that strengthen Balinese Customary Law. The method uses descriptive approach to describe precisely the properties of an individual, situation, symptom or certain group to determine the presence or absence of a relationship between a symptom and other symptoms in society. Through an Empirical approach, with the reality that occurs in the community according to the Awig-awig of the Padang Luwih Traditional village, states that people who have left Hinduism (Ninggal Kedaton) no longer get inheritance rights in the family, because they cannot carry out their obligations both in life in the Customary community, Family, and obligations to ancestors in Mrajan Agung. Inheritance in Balinese customary law does not solely contain the rights of the heirs to the inheritance property, but more than that, the most important is the obligation of the heirs to the testator. The obligation of the heirs is a consequence of the rights they receive.